Cognitive and Global Functioning in Patients With First-Episode Psychosis Stratified by Level of Negative Symptoms. A 10-Year Follow-Up Study - Engen, Magnus Johan; Vaskinn, Anja; Melle, Ingrid; Færden, Ann; Lyngstad, Siv Hege; Flaaten, Camilla Bärthel; Widing, Line Hustad; Wold, Kristin Fjelnseth; Åsbø, Gina; Haatveit, Beathe; Simonsen, Carmen; Ueland, Torill (Frontiers in Psychiatry, 2022)
Negative and cognitive symptoms are core features of schizophrenia that are correlated in cross-sectional designs. To further explore the relationship between these critical symptom dimensions we use a method for stratifying participants based on level and persistence of negative symptoms from absent to sustained levels over a 10-year follow-up period. We investigate associations with cognitive performance and level of global functioning. First-episode psychosis (FEP) participants (n=102) and healthy controls (n=116) were assessed at baseline and follow-up. A cognitive battery consisting of 14 tests derived into four domains and a composite score were used in the analyses. FEP participants were stratified based on negative symptom items from the Positive and Negative Syndrome Scale (PANSS-R) into four groups with either no, mild, transitory or sustained symptoms over the 10-year follow-up period. Global functioning was measured with Global Assessment of Functioning Scale-Split version. Multivariate and univariate analyses of variance were used to explore between-group differences in level and course of cognitive and global functioning. A multivariate analysis with four cognitive domains showed significant group differences when including healthy controls and the negative symptom groups. The no and mild negative symptoms groups outperformed the sustained negative symptom group on verbal learning and memory. Participants with no negative symptoms also outperformed the group with sustained negative symptoms on the cognitive composite score. Significant improvements on verbal learning and memory, executive functioning and the cognitive composite were detected for the entire sample. No differences in cognitive course were detected. There was a significant improvement in global functioning as measured by the GAF-F over the follow-up period (p < .001), without any time x group interactions (p = .25). Participants with sustained negative symptoms had a significantly lower level of global functioning at 10-year follow-up with an additional independent effect of the cognitive composite score, compared to all other groups. Individuals with an early illness course characterized by absence of negative symptoms form a group with better cognitive and functional outcomes than the impairments typically associated with schizophrenia. Individuals with sustained levels of negative symptoms may require a combined focus on both negative and cognitive symptoms.